BRAND-RELATED MARKETING METRICS - Ćirić, Saša (International Journal of Economic Practice and Policy, 2024)
Adequate measurement is crucial for brand management but represents a real challenge for marketers. Choosing adequate indicators to measure the effectiveness and efficiency of brand investments is one of the prerequisites for brand success. The most common problem is the sensitivity of individual indicators to recognize the level of brand presence in the minds of customers or consumers and the effectiveness of certain indicators in terms of long-term brand investment. This paper presents the most commonly used marketing indicators related to the brand and the advantages and disadvantages of influencing its value. Through the analysis of secondary data, using the desk research method, the author will look at the theoretical framework for selecting and defining marketing metrics related to the brand through relevant literature and scientific papers dealing with this topic. Finally, the author will recommend how the critical determinants of brand value should be measured and the selection of adequate indicators regarding the effectiveness and efficiency of brand investment.